2022
DOI: 10.1155/2022/4551094
|View full text |Cite
|
Sign up to set email alerts
|

Level of Art Flow among Faculty Students of Design and Applied Arts at Taif University

Abstract: The current study sought to determine the flow level of students at Taif University’s College of Designs and Applied Arts and the disparities in average student grades based on gender, specialization, and academic level. The sample was drawn randomly from Taif University’s College of Designs and Applied Arts and included (51) male and (138) female students majoring in arts, graphic design, interior design, fashion design, and textiles. The flow scale was produced by Al-Ghamdi (2021). Overall, there is an avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…As a result, participants reach a certain level of proficiency in graphic design, which they can utilize in marketing or designing for small businesses. The results of the current research agree with those of a study by Aldhorman (2022) in terms of the program's success in developing graphic artistic performance skills. They also agree with the results of a study by Enriquez (2020), which revealed that there are similarities in several tools, even if their names are different, which makes it easy to use any of them or move from one application to another.…”
Section: Tablesupporting
confidence: 87%
See 1 more Smart Citation
“…As a result, participants reach a certain level of proficiency in graphic design, which they can utilize in marketing or designing for small businesses. The results of the current research agree with those of a study by Aldhorman (2022) in terms of the program's success in developing graphic artistic performance skills. They also agree with the results of a study by Enriquez (2020), which revealed that there are similarities in several tools, even if their names are different, which makes it easy to use any of them or move from one application to another.…”
Section: Tablesupporting
confidence: 87%
“…There were also statistically significant differences between the average number of degrees of the experimental research sample members before and after the application of the program in favor of the post-application. Aldhorman (2022) aimed in his study to measure the effectiveness of a proposed program for developing graphic design skills for female students at Taif University by focusing on how to prepare a proposed educational program based on making use of the technical characteristics and advantages to develop graphic artistic performance among the female students. The fourth is in the College of Designs and Home Economics, Department of Electronic Drawing, at Taif University.…”
Section: Graphic Design Toolsmentioning
confidence: 99%